2022
DOI: 10.1016/j.jaut.2021.102778
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin – from iron, through inflammation and autoimmunity, to COVID-19

Abstract: While it took decades to arrive to a conclusion that ferritin is more than an indicator of iron storage level, it took a short period of time through the COVID-19 pandemic to wonder what the reason behind high levels of ferritin in patients with severe COVID-19 might be. Unsurprisingly, acute phase reactant was not a satisfactory explanation. Moreover, the behavior of ferritin in patients with severe COVID-19 and the subsequent high mortality rates in patients with high ferritin levels necessitated further inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
1
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 140 publications
(158 reference statements)
5
80
1
8
Order By: Relevance
“…Ferritin promotes the release of proinflammatory mediators and increases the inflammatory burden, resulting in a vicious circle. Ferritin achieves this by activation of NF-ԟB, leading to a positive regulation of ferritin gene transcription [ 32 ]. In our study, its impact appears not to have been very significant on the risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin promotes the release of proinflammatory mediators and increases the inflammatory burden, resulting in a vicious circle. Ferritin achieves this by activation of NF-ԟB, leading to a positive regulation of ferritin gene transcription [ 32 ]. In our study, its impact appears not to have been very significant on the risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…The role of iron in kidney diseases has recently been emphasised, and more precise localisation of ferritin throughout the kidney may tell us more about its functions in (pato)physiology ( 5 , 25 , 26 , 27 , 28 ). However, protein expression in organs detected by western blotting in our study has yet to be confirmed by in situ distribution in order to reveal a more precise expression pattern.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings have shown strong ferritin staining of interstitial cells irregularly present in all kidney zones. We assume that it could be associated with macrophages ( Figures 6 and 7, c and d ), as macrophages have recently been recognised as a new source of serum ferritin ( 25 , 28 ). This could be relevant for our positive findings of ferritin in aged rats.…”
Section: Resultsmentioning
confidence: 99%
“…We highlighted that beyond the first three months after contagion, individuals who recovered from SARS-CoV-2 infection are characterized by the persistence of a systemic inflammatory state and are at high risk for developing somatization, depression, anxiety, and sleep disturbances. In particular, we found out that the median baseline serum LDH and ferritin levels were significantly higher three months after SARS-CoV-2 infection [ 16 ]. Interestingly enough, ferritin value was strongly correlated with sleep disorders, independently of gender.…”
Section: Discussionmentioning
confidence: 99%